Transformation of Religious Fundamentals for Students in Religious Studies at Balai Pengajian Guru Sekumpul, Pidie Regency - Saputra, Nanda (Institute of Education and Social Research, 2023)
Religious diversity is one of the significant aspects of Indonesian society. Among the various religions practiced in Indonesia, Islam has the largest number of followers. In this context, Islamic boarding schools or